Mild and selective catalytic oxidation of organic substrates by a carbon nanotube-rhodium nanohybrid1. Issue 9 (17th September 2015) - Donck, Simon; Gravel, Edmond; Li, Alex; Prakash, Praveen; Shah, Nimesh; Leroy, Jocelyne; Li, Haiyan; Namboothiri, Irishi N. N.; Doris, Eric
<x xml:space="preserve">Abstract</x> A heterogeneous catalyst was assembled by stabilization of rhodium nanoparticles on carbon nanotubes.